2015
DOI: 10.4103/0366-6999.156078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Administration of Liposomal Prostaglandin E1 on Microcirculation in Patients with ST Elevation Myocardial Infarction Undergoing Primary Percutaneous Intervention

Abstract: Background:Several studies have demonstrated that primary percutaneous coronary intervention (PCI) can result in reperfusion injury. This study aims to investigate the effectiveness of liposomal prostaglandin E1 (Lipo-PGE1, Alprostadil, Beijing Tide Pharmaceutical Co., Ltd.) for enhancing microcirculation in reperfusion injury. In addition, this study determined the optimal administration method for acute ST elevation myocardial infarction (STEMI) patients undergoing primary PCI.Methods:Totally, 68 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…[24][25][26][27]. Furthermore, PGE1 improved the myocardial microcirculation and alleviated apoptosis of myocardial cells [28,29]. These findings indicate that alprostadil may have an anti-inflammatory effect, although its molecular mechanisms are not exactly clear.…”
mentioning
confidence: 99%
“…[24][25][26][27]. Furthermore, PGE1 improved the myocardial microcirculation and alleviated apoptosis of myocardial cells [28,29]. These findings indicate that alprostadil may have an anti-inflammatory effect, although its molecular mechanisms are not exactly clear.…”
mentioning
confidence: 99%
“…Of the 6 included studies, 3 involved patients receiving elective PCI, [ 25 27 ] 1 involved primary PCI, [ 28 ] 1 involved elective mitral valve surgery, [ 29 ] and 1 involved elective CABG or valve surgery [ 30 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2 other studies, [ 25 , 26 ] patients were administered 20 μg/day PGE1 starting at least 48 hours before PCI and continuing for 5 days or starting 3 days before PCI and continuing for 4 days after PCI, respectively. Moreover, one [ 28 ] study described the administration of 20 μg PGE1 immediately after coronary angiography and another [ 27 ] administered 0.005 to 0.03 μg/kg/min PGE1, starting at least 2 hours before PCI and continuing for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that intravenous administration of alprostadil in patients with ST elevation myocardial infarction undergoing primary PCI could improve myocardial microcirculation, reduce myocardium non-flow area, and decrease major adverse cardiac events (MACE). 32 Interestingly, alprostadil injection also provides cardioprotection effects on elective PCI patients with unstable angina, which reduces the incidence rates of periprocedural myocardial injury, and decreases pro-inflammatory factor secretion. 33 In human chronic ischemia heart disease, alprostadil effectively stimulates neoangiogenesis in infarct areas adjacent to the viable myocardium.…”
Section: Discussionmentioning
confidence: 99%